Pengaruh Pelatihan Kognitif Perilakuan Dan Pola Makan Rasulullah Dalam Meningkatkan Pengendalian Perilaku Makan Pada Wanita Obesitas - Putri, Syuri Permana; , Dr. Moordiningsih, M.Si., Psi; , Wisnu Sri Hertinjung, S.Psi., M.Psi (2015)
Obesity Is a disorder or diasease characterized by the accumulation of fat in the body excessively. One of the causes of obesity are excessive eating behavior pattern. Person who are overweight more responsive than normal weigth person to the terms of external hungry, such as taste and smell of food, or for mealtime. Person with obese tend to eat when they feels like eating and not eating when they feel hungry. This excessive diet that makes a person difficult to get out of obesity, because the individual does not have the self control and a hard motivation to lose weight. This study aims to look at the effect of cognitive behavioral training compared with the Diet Rasulullah on the obese women's eating behavior control. The hypothesis proposed in this study is no difference between the effects of cognitive behavioral training and diet Rasulullah on increase the obese women's eating behavior control. Participants of this study were selected based on the score somewhat lower and lower in scale of the obese women's eating behavior control were stratified I-III. Obtained 12 participants were then randomly divided into 3 groups; 4 participants for experimental group with cognitive behavioral training, 4 participants on experimental comparison group who received treatment with diet Rasulullah, and 4 participants on the control group. Result of data analysis for cognitive behavioral training using Wilcoxon Signed-Rank obtaned Z value -1,841 and significance level 0,033. Result of data analysis for diet Rasulullah using Wilcoxon Signed-Rank obtained Z value -1,826 with significance level 0,034. Hal ini menunjukkan terjadi peningkatan pengendalian perilaku makan pada wanita obesitas. Data analysis cognitive behavioral training group and diet Rasulullah group using Mann Whitney U Test were equally obtained the Z value -0,309 and a significance level 0,010. This shows that there is a difference between the experimental group and the control group, the experimental group score higher than the control group score. Based on the study's results, it was concluded that cognitive behavioral training and diet Rasulullah equally influential increase the obese women's eating behavior control. Keyword: Cognitive Behavioral Training, Obesity, Obese Women, Eating Behavior Control, Diet Rasulullah, Wilcoxon Signed-Rank, Mann Whitney U Test